IOT-Based Energy Monitoring System for Energy Conservation - Siti Aisyah, Mohd; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; Nurasyikin, Misdan (EDP Sciences, 2023)
The aim of this project is to develop an Internet of Things (IoT) based Energy Monitoring System to reduce energy waste and cutting down energy cost. Therefore, it needs a system which provide efficient energy consumption management. For the starting of designing an IoT-based Energy Monitoring System, different sensor and calculated AC measurement methods were studied. The development of this system is to integrate each of the sensor, energy measuring device and IoT system into one complete module. The concept of Wireless Sensor Network (WSN) was implemented in this project. The WSN obtained data information from sensor and send them to the cloud through the IoT network for cloud storage of the ThingSpeak platform. The system contains two input signal which is voltage and current. The device that transfers the data or information from the energy monitoring device to the cloud storage is the ESP8266 Wi-Fi module. The output is the energy consumption that has been used according to the real-time data measurement. Lastly, the data that is transmitted to the cloud can be monitored through the mobile application ThingView. In conclusion, this system is necessary because it can control and manage energy consumption to avoid wastage and promote energy conservation.